2006
DOI: 10.1165/rcmb.2005-0386oc
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Activation by Epidermal Growth Factor Mediates Oxidant-Induced Goblet Cell Metaplasia in Human Airway Epithelium

Abstract: Mucus overproduction in inflammatory and obstructive airway diseases is associated with goblet cell (GC) metaplasia in airways. Although the mechanisms involved in GC metaplasia and mucus hypersecretion are not completely understood, association with oxidative stress and epidermal growth factor receptor (EGFR) signaling has been reported. To explore the mechanisms involved in oxidative stress-induced GC metaplasia, cultures of differentiated normal human bronchial epithelial cells grown at the air-liquid inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 86 publications
10
110
1
Order By: Relevance
“…Biologically, goblet cells are associated with the EGFR-signaling pathway, which results in goblet cell metaplasia and mucin secretion from the cells (13). In the present study, it was found that the number of EGFR-positive lid wipers was significantly greater in the rebamipide group compared EGFR, epithelial growth factor receptor; +, positive; -, negative.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Biologically, goblet cells are associated with the EGFR-signaling pathway, which results in goblet cell metaplasia and mucin secretion from the cells (13). In the present study, it was found that the number of EGFR-positive lid wipers was significantly greater in the rebamipide group compared EGFR, epithelial growth factor receptor; +, positive; -, negative.…”
Section: Discussionsupporting
confidence: 48%
“…The EGFR-signaling pathway serves an important role in goblet cell proliferation and mucin secretion from the cells. EGFR signaling contributes to the underlying mechanisms of goblet cell metaplasia and mucus hypersecretion in the epithelia of human airways (13). Several previous studies have demonstrated that transactivation of EGFR enhances mucin secretion in rat conjunctival goblet cells (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…More recent work has started to delineate the mechanisms by which oxidative stress enhances mucus production and mucus cells metaplasia. Specifically, work by Casalino-Matsuda et al demonstrated that in differentiated bronchial epithelial cells, reactiveoxygen intermediates (ROI) activated tissue kallikrein, a serine protease related to the formation of kinins, which in turn induced EGFR activation and enhanced expression of MUC5AC [45]. In addition, recombinant tissue kallikrein was able to mimic the effects of ROI with regards to MUC5AC expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recombinant tissue kallikrein was able to mimic the effects of ROI with regards to MUC5AC expression. Furthermore, catalase was an inhibitor of tissue kallikrein [45], suggesting that decreased catalase activity could enhance tissue kallikrein activity and therefore be a potential mechanism by which Se-deficiency enhanced MUC5AC expression and mucus levels in bronchial epithelial cells. Interestingly, preliminary analysis of gene array data comparing Se-deficient and Se-adequate bronchial epithelial cells indicate that kallikrein expression may be enhanced in Se-deficient epithelial cells (data not shown), which we are currently examining further.…”
Section: Discussionmentioning
confidence: 99%
“…Because dual oxidases are expressed in airway epithelial cell surface, dual oxidase-1 (Duox-1) may be involved in TACE activation (78). Other enzymes besides TACE that can also cleave pro-EGFR ligands to activate MUC5AC include MMPs, dis-integrin and metalloproteinase domain proteins (ADAMs), and tissue kallikrein (TK) (89,90). Downstream of EGFR, the mechanism that leads to MUC5AC expression can involve ERK activation with subsequent binding of transcription factors Sp1 (18) and Fra-2 to the MUC5AC promoter (91).…”
Section: Transcriptional Activation Of Muc5ac Through Epidermal Growtmentioning
confidence: 99%